Studi Komunikasi Pengungkapan Diri Odha (Studi Orang dengan HIV/AIDS Melalui Instagram) - Sandinatha, Alvina Oeyta; Azeharie, Suzy (Koneksi, 2022)
In everyday life, people build relationships with each other. An important aspect of social skills is self-disclosure. The HIV/AIDS virus is one of the social problems in society. People living with HIV/AIDS (PLWHA) tend to be stigmatized and discriminated against by society. People living with HIV/AIDS face the risk of discrimination and stigma when they reveal themselves. This makes PLWHA hesitate to reveal themselves. Instagram is one of the most famous social media in the world. Instagram is a platform that can help PLWHA express themselves. This study aims to find out how PLWHA express themselves through Instagram. This research uses a qualitative approach, with a case study method. A case study was conducted on three PLWHA. Data collection was carried out using in-depth interviews with three PLWHA who had disclosed their status to Instagram. In addition, interviews were also conducted with health promoters in the field of HIV/AIDS as a research triangulator. This study found that before PLWHA revealed their HIV/AIDS status to Instagram, they felt cognitive dissonance in the form of fear of rejection and stigma. This dissonance prevents people living with HIV/AIDS from expressing themselves. Support from the closest people greatly influences PLWHA to be able to express themselves. After revealing themselves on Instagram, people living with HIV/AIDS feel joy and love themselves even more. Self-disclosure on Instagram being done by uploading content in the form of photos, videos, and Instagram story features. Instagram provides discussion space for PLWHA. Dalam  kehidupan sehari-hari, orang membangun hubungan satu sama lainnya. Aspek penting dari kemampuan sosial adalah pengungkapan diri. Virus HIV/AIDS merupakan salah satu masalah sosial di  masyarakat. Orang dengan HIV/AIDS (ODHA) cenderung mengalami stigmatisasi dan diskriminasi oleh masyarakat. Orang yang hidup dengan HIV/AIDS menghadapi risiko diskriminasi dan stigma ketika mereka mengungkapkan diri. Hal ini membuat ODHA ragu untuk mengungkapkan dirinya. Instagram adalah salah satu media sosial paling terkenal di dunia. Instagram merupakan salah satu  platform yang  dapat membantu ODHA mengekspresikan dirinya. Penelitian ini bertujuan untuk mengetahui bagaimanakah ODHA mengungkapkan diri melalui Instagram. Penelitian ini menggunakan pendekatan kualitatif, dengan metode studi kasus. Studi kasus dilakukan terhadap tiga ODHA. Pengumpulan data dilakukan menggunakan wawancara mendalam dengan tiga ODHA yang sudah mengungkapkan statusnya ke Instagram. Selain itu wawancara juga dilakukan kepada promotor kesehatan bidang HIV/AIDS sebagai triangulator penelitian. Penelitian ini menemukan bahwa sebelum ODHA mengungkapkan status HIV/AIDS ke Instagram, mereka merasakan disonansi kognitif berupa ketakutan terhadap penolakan dan stigma. Disonansi ini menghambat ODHA dalam mengungkapkan diri. Dukungan dari orang terdekat sangat mempengaruhi ODHA agar bisa mengungkapkan dirinya. Setelah mengungkapkan diri di Instagram, ODHA merasakan sukacita dan semakin mencintai dirinya sendiri. Pengungkapan diri di Instagram dilakukan dalam bentuk unggahan konten berupa foto, video, dan fitur Instagram story. Instagram memberi ruang diskusi untuk ODHA.